Efficacy and reliability of various grades of processed honey as a fixative: A comparative study - Kunal Sah; B J Janardhan; Raj Kumar Srivastava; Sanjay Nigam (Wolters Kluwer Medknow Publications, 2021)
Introduction: Ethanol is a traditional cytofixative which is widely used for oral exfoliative cytology. Due to its limitations, a search of better, eco-friendly, and cost-effective fixative was explored. The present study was conducted to evaluate the efficacy and reliability of 10%, 20%, and 30% processed honey as a cytofixatives, and was compared with that of 95% ethanol. Materials and Methods: Four oral smears were obtained from each individual (n = 80) by gently scraping the buccal mucosa. One slide was fixed in ethanol (95%) and the other in various grades of processed honey (10%, 20%, and 30%), and stained with Papanicolaou stain. Two separate pathologists who were kept in blind for the fixative used evaluated the slides based on the five parameters (cell morphology, nuclear and cytoplasmic staining, clarity, and uniformity of staining). Results: In the present study, it was observed that 20% of processed honey showed overall good results, followed by (95% alcohol) and (10% honey). However, poor results were observed in (30% honey). When compared, no statistically significant difference was observed between the groups. Conclusion: The present study offers an innovative application using honey as a cytofixative. Honey in lower concentration is an excellent alternative to ethanol as a cytofixative.